Two views on neutral money: Wieser and Hayek versus Menger and Mises. Issue 5 (2nd September 2020) - Salerno, Joseph T.; Dorobat, Carmen Elena; Israel, Karl-Friedrich
Abstract: Neutral money plays a central role in contemporary macroeconomic theory, and is a live issue in recent monetary policy discussions. We challenge the opinion that Hayek's writings on neutral money have been influenced by, and are similar to, the work of Menger and Mises. We show, first, the significant alternative influence of Friedrich von Wieser on Hayek's work on the subject. Second, we rehabilitate a neglected method of monetary theorising specific to Menger and Mises that rejects money neutrality both as a tool for investigating monetary phenomena and as the standard by which monetary regimes, and the market economy itself, should be evaluated. Examining this chapter in the history of economic thought can aid in a deeper reconsideration of the doctrinal foundations of modern monetary theory and policy.